EDUCATION SYSTEM NEEDS TO INFORMATION TECHNOLOGY - Оноприенко, В. И. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
New aspects of the education systems caused by the unprecedented progress of information and communication technologies and globalization are considered through the pryzm of interrelated values of democracy and education.